Definition of curriculum and approach: study of a training course for teachers of non-formal education in NGOs - Deivis Perez (Universidade Federal de Santa Maria, 2014)
This article presents a research aimed to analyze the approach and the definition of guiding curriculum of teacher training for work in the non-formal education in non-governmental organizations(NGOs). We opted for a qualitative approach and case study of Teacher Training Course for NGOs, developed by Ong São Paulo-SP. The research instruments were: analysis of documents of the course, interviews with trainers and coordinator and literature review. In this course, curriculum is defined as a path to be followed by students and instructors and the coordinator of the subjects studied. We adopted the so-called Integrated Curriculum, in which teaching occurs by the study of problem situations and integrators of learning projects. At the end, we suggest improving the course and following that information, it is hoped, one will support the production of further comparative research.